S-commerce buying decision model for second-hand products in Thailand: A conceptual framework - Auttaput, Tharinee; Chiyasoonthorn, Wornchanok; Chaveesuk, Singha (My University, 2018)
In Thailand, social commerce (s-commerce) is a new development in e-commerce that uses social media to empower customers to interact with sellers and other buyers on the Internet. The advancement of Web technology and social media platform gives rise to s-commerce which can act like a mechanism for businesses and customers to interact. S-commerce reestablished the social aspect of shopping in e-commerce. It especially increases the amount of social behavior in the online environment. In addition, the nature of the second-hand economy has changed significantly with the beginning of online technology, services, and platforms, i.e., the way second-hand product trade is implanted has changed by s-commerce. Inevitably, the related issues of social network marketing and trust between buyers and sellers have been also been a focus of attention for researchers in order to expand the current understanding of this phenomenon, especially regarding technological marketing and users' trust. Accordingly, the main objective of this study was to systematically review and develop a conceptual framework of s-commerce buying decision model for second-hand product trade in Thailand. This study theorizes the nature of social aspect of online s-commerce behavior. Researchers employ a set of digital marketing mix and a trust model for consumers' Internet shopping that could explain current online purchase behavior. Finally, this proposed model provides potential factors that affect the buying-decision behaviors of second-hand products through s-commerce in Thailand.
Keywords: Buying behaviour; Digital marketing mix; S-commerce; Second-hand economy; Second-hand products; Trust